Pairwise approach for analysis and reporting of child’s free sugars intake from a birth cohort study - Nguyen, H.V.; Ha, D.H.; Dao, A.T.M.; Golley, R.K.; Scott, Jane; Spencer, J.; Bell, L.; Devenish-Coleman, Gemma; Do, Loc (2022)
Objectives: The prospective cohort design is an important research design, but a common challenge is missing data. The purpose of this study is to compare three approaches to managing missing data, the pairwise (n = 1386 children), the partial or modified pairwise (n = 1019) and the listwise (n = 546), to characterize the trajectories of children's free sugars intake (FSI) across early childhood.